Madeira Wine Contributions for Madeira Island Sustainable Tourism - Abreu, Cristina; Gonçalves, Ana; Jesus, Ana; Rodrigues, Beatriz; Santos, Jessica; Teives, Marcelo; Garcias, João (Journal of Tourism, Sustainability and Well-being, 2019)
Madeira Island is an Atlantic island, that was colonized by Portuguese in the year 1420. The first vineyards introduced in the island were Malmsey, imported from Greece, in the XV century leading to the production of liquorish wine, Madeira Wine. Recently, table wine is also produced. The present study aims to understand the contribution of Madeira Wine production on touristic experiences as well its role on landscape maintenance, local identity, natural resources conservation, job creation and economy. A questionnaire survey was delivered to tourists, and two too semi-structured interviews: to a local wine producer- Quinta do Barbusano and a Chef- Dúlio Freitas respectively, on December 2018. In Quinta do Barbusano two red wines, two white wines and one Rosé are produced. Since 2018, Quinta do Barbusano promotes a new product “Wine tourism”, offering wine tastings, farm’s visits and a lunch providing regional gastronomy, using local products. Secondary data was also consulted, such as governmental and national Official statistical data, concerning Madeira Wine production and Madeira Wine commercialization. The results presented in this study reflect that Madeira Wine production can play a key role in sustainable tourism. The authors also featured as research limitations the need to improve survey sample size, as well the number of interviews in order to reach particularly relevant actors in this field.